Halide solid electrolyte composite material, preparation method thereof and battery

By adopting a core-shell structure in halide solid electrolytes, combining crystalline and amorphous halide electrolytes, the conductivity, potential and air stability of the electrolyte are solved, the battery performance is improved and the preparation cost is reduced. Mass production.

CN119181847APending Publication Date: 2024-12-24ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411335093.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing halide solid electrolytes cannot take into account both ionic conductivity, potential stability and air stability, resulting in poor battery performance and high production cost.

Method used

A halide solid electrolyte composite material with a core-shell structure is used, and a crystalline halide electrolyte is used as the core core and amorphous halide electrolyte is used as the cladding layer. A uniform cladding layer is formed by mixing, stirring, drying and heat treatment. Improve the ionic conductivity, oxidation potential and air stability of the electrolyte.

Benefits of technology

It achieves high ionic conductivity, stable oxidation potential and good air stability, improves the rate performance and cycle stability of the battery, reduces the preparation environment requirements and costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181847A_ABST
    Figure CN119181847A_ABST
Patent Text Reader

Abstract

The invention relates to the field of new energy batteries, in particular to a halide solid electrolyte composite material, a preparation method thereof and a battery, the halide solid electrolyte composite material comprises first halide solid electrolyte particles and a coating layer coating the surfaces of the first halide solid electrolyte particles; wherein the first halide solid electrolyte particles are crystalline halide electrolyte particles; the coating layer comprises second halide solid electrolyte particles, and the second halide solid electrolyte particles are amorphous halide electrolyte particles. The halide solid electrolyte composite material disclosed by the invention has relatively high ionic conductivity and also has relatively high oxidation potential and relatively high air stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy batteries, and in particular to a halide solid electrolyte composite material and a preparation method thereof and a battery. Background Art

[0002] Safety accidents involving new energy vehicles occur frequently, mainly because traditional lithium-ion batteries require the use of flammable organic solvents as electrolytes, which poses a huge safety hazard. The usual improvement methods cannot completely solve this problem. In comparison, solid-state lithium-ion batteries using solid electrolytes have greater safety advantages. The use of solid electrolytes can not only fundamentally solve the safety problems of lithium-ion batteries, but is also expected to greatly simplify the manufacturing and packaging process, and improve the energy density, reliability, and design freedom of the battery. Therefore, it is necessary to ensure the high ionic conductivity, high potential stability, and high air stability of the solid electrolyte.

[0003] Among inorganic electrolyte materials, the current mainstream electrolyte systems are mainly divided into three systems: oxides, sulfides and halides. Among them, oxide electrolytes have high oxidation potentials and are stable to high-voltage ternary positive electrode materials, but their ionic conductivity is low, and they have high rigidity and poor ductility, resulting in large contact impedance with positive electrode materials and poor battery performance. Sulfide electrolytes usually have high ionic conductivity and good ductility, and can form a relatively dense physical contact with positive and negative electrode materials; but the oxidation potential is low. When the voltage is greater than 3V, it is easy to decompose and produce side reactions, affecting the performance of the battery ring; the air stability is poor, and it is very easy to react with moisture in the air when exposed to air to generate toxic H2S gas, and the performance drops sharply at the same time, so it has strict requirements on the control of the preparation environment, usually requiring an environmental dew point of ≤-70°C, which is not conducive to large-scale batch production. In comparison, halide electrolytes such as LiMOCl4 (M is Ta or Nb), LiTaCl5N (N=F - or 2- ) are several types of solid electrolyte materials that have recently attracted attention. Their oxidation potentials are higher than those of sulfides, and theoretically they are more compatible with the positive electrode, but they still have the following problems: For example, the crystalline LiNbOCl4 electrolyte has good rate performance but poor cycle performance when matched with the high-nickel ternary positive electrode, and its air stability is poor. When exposed to air, it is easy to react with moisture in the air to generate HCl gas, and its performance is seriously reduced; for example, the amorphous LiTaCl5O 0.5 The electrolyte is actually matched with a high-nickel ternary positive electrode, although the cycle performance is good, the rate performance is poor. Moreover, the abundance of Ta is low and the price is expensive, which is not conducive to the large-scale preparation of the electrolyte itself, the subsequent positive electrode and the battery. Summary of the invention

[0004] In view of this, the present invention is committed to providing a halide solid electrolyte composite material and a preparation method and a battery thereof, so as to solve the problem in the prior art that the ionic conductivity, potential stability and air stability of the halide solid electrolyte cannot be taken into account at the same time.

[0005] In order to solve the above technical problems, this application is implemented as follows:

[0006] A first aspect of the present invention provides a halide solid electrolyte composite material, the halide solid electrolyte composite material comprising a first halide solid electrolyte particle and a coating layer coated on the surface of the first halide solid electrolyte particle;

[0007] Wherein, the first halide solid electrolyte particles are crystalline halide electrolyte particles;

[0008] The coating layer includes second halide solid electrolyte particles, and the second halide solid electrolyte particles are amorphous halide electrolyte particles.

[0009] Optionally, the first halide solid electrolyte particles include LiMOCl4, wherein M is selected from Ta and / or Nb; and / or, the second halide solid electrolyte particles include LiTaCl5N 1 / n , wherein N is selected from at least one of Cl, Br, F and O, and n=1 or 2.

[0010] Optionally, the mass ratio of the coating layer material to the first halide solid electrolyte particles is (0.001-0.1):1.

[0011] Optionally, the D50 of the halide solid electrolyte composite material particles is 10.1-22 μm; optionally, the D50 of the first halide solid electrolyte particles is 10-20 μm; and the D50 of the second halide solid electrolyte particles is 0.05-1 μm.

[0012] A second aspect of the present invention provides a method for preparing a halide solid electrolyte composite material, the method comprising the following steps:

[0013] S1, mixing a crystalline halide electrolyte suspension and an amorphous halide electrolyte suspension and performing a dispersion treatment to obtain a first material; stirring the first material to obtain a second material;

[0014] S2, drying the second material to obtain a precursor;

[0015] S3, subjecting the precursor to heat treatment and grinding treatment.

[0016] Optionally, the crystalline halide electrolyte suspension comprises a crystalline halide electrolyte and a first organic solvent; the solid content of the crystalline halide electrolyte suspension is 20-50%; optionally, the first solvent is selected from at least one of alkane solvents, benzene solvents, ether solvents and ketone solvents; preferably, the first solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone; and / or, the amorphous halide electrolyte suspension comprises an amorphous halide electrolyte and a second organic solvent; the solid content of the amorphous halide electrolyte suspension is 0.5-20%; optionally, the second solvent is selected from at least one of alkane solvents, benzene solvents, ether solvents and ketone solvents; preferably, the second solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone.

[0017] Optionally, in step S1, the mixing and dispersing treatment are carried out in a first inert atmosphere; the conditions of the dispersing treatment include: a dispersing temperature of 50 to 80°C and a dispersing time of 2 to 6 hours; the stirring treatment is carried out in a second inert atmosphere; the conditions of the stirring treatment include: a stirring temperature of 50 to 80°C and a stirring time of 2 to 6 hours.

[0018] Optionally, in step S2, the drying treatment is carried out in a third inert atmosphere; the drying treatment is a freeze-drying treatment, and the conditions of the freeze-drying treatment include: a freezing temperature of -100 to -20°C, a drying time of 6 to 12 hours, and a pressure of -95 to -50Pa.

[0019] Optionally, in step S3, the heat treatment is performed in a fourth inert atmosphere; the conditions of the heat treatment include: a temperature of 100 to 250° C., a heating rate of 1 to 2° C. / min, and a time of 2 to 4 hours.

[0020] A third aspect of the present invention provides a battery, wherein the battery contains a solid electrolyte, wherein the solid electrolyte includes the above-mentioned halide solid electrolyte composite material and / or the halide solid electrolyte composite material prepared according to the above-mentioned method.

[0021] Through the above technical solution, the beneficial technical effects of the present invention are:

[0022] (1) The halide solid electrolyte composite material of the present invention selects a crystalline halide electrolyte with high ionic conductivity as the core material and an amorphous halide electrolyte with relatively high ionic conductivity as the coating material, which can effectively ensure that the halide solid electrolyte composite material has a relatively high ionic conductivity, and is conducive to achieving high-rate charge and discharge performance of the battery.

[0023] (2) The halide solid electrolyte composite material of the present invention uniformly coats a layer of amorphous halide electrolyte on the surface of crystalline halide electrolyte particles. The higher oxidation potential of the amorphous halide electrolyte can be used to effectively improve the oxidation potential of the target electrolyte, enhance its contact stability with the positive electrode material, and thus improve the battery energy density and cycle stability.

[0024] (3) The halide solid electrolyte composite material of the present invention utilizes the high air stability of the amorphous halide electrolyte of the coating layer to effectively improve the air stability of the target electrolyte, thereby reducing the preparation environment requirements and manufacturing costs, and making it easier to achieve large-scale mass production.

[0025] (4) The core-shell material selected for the halide solid electrolyte composite material of the present invention is an amorphous halide electrolyte. Compared with the crystalline electrolyte, which has the disadvantages of high grain boundary resistance, poor processability and high cost, the amorphous electrolyte has the advantages of being softer, easier to manufacture, having low grain boundaries, a wider range of composition variations and isotropic ion conduction, thereby making the halide solid electrolyte composite material have higher ductility.

[0026] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0028] Figure 1 Shown are the XRD spectra of the solid electrolyte materials prepared in Examples 6 to 11 and Comparative Example 1. DETAILED DESCRIPTION

[0029] The present invention discloses a halide solid electrolyte composite material and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0030] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0031] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] In order to solve the problem that the ionic conductivity, potential stability and air stability of halide solid electrolytes in the prior art cannot be taken into account at the same time, the present invention adopts the following technical solution:

[0036] A first aspect of the present invention provides a halide solid electrolyte composite material, the halide solid electrolyte composite material comprising a first halide solid electrolyte particle and a coating layer coated on the surface of the first halide solid electrolyte particle;

[0037] Wherein, the first halide solid electrolyte particles are crystalline halide electrolyte particles;

[0038] The coating layer includes second halide solid electrolyte particles, and the second halide solid electrolyte particles are amorphous halide electrolyte particles.

[0039] The halide solid electrolyte composite material of the present invention has a core-shell structure, wherein the core material is a crystalline halide electrolyte, and the coating layer material is an amorphous halide electrolyte, that is, a layer of amorphous halide electrolyte with high oxidation potential, high air stability and certain ionic conductivity is uniformly coated on the surface of crystalline halide electrolyte particles with high ionic conductivity, thereby achieving a target electrolyte with both high oxidation potential and high air stability while having high ionic conductivity.

[0040] According to the present invention, the first halide solid electrolyte particle may include LiMOCl4, wherein M is selected from Ta and / or Nb. As a preferred embodiment of the present invention, considering element abundance and cost, the first halide solid electrolyte particle includes LiNbOCl4.

[0041] According to the present invention, the second halide solid electrolyte particles may include LiTaCl5N 1 / n , wherein N is selected from at least one of Cl, Br, F and O, and n=1 or 2. As a preferred embodiment of the present invention, in order to further improve ionic conductivity and air stability, the second halide solid electrolyte particle is LiTaCl5O 0.5 .

[0042] According to the present invention, the mass ratio of the coating material to the first halide solid electrolyte particles can be (0.001-0.1):1. Exemplarily, the mass ratio of the coating material to the first halide solid electrolyte particles can be any value in 0.001:1, 0.005:1, 0.01:1, 0.05:1 and 0.1:1 or any value in the range of any two of the above values. The appropriate coating amount enables the target electrolyte to have both high ionic conductivity and high antioxidant potential and air stability. If the coating layer is too thick, the ionic conductivity of the target electrolyte will be low, thereby affecting its rate performance; if the coating layer is too thin, the target electrolyte will have a low antioxidant potential and poor air stability. As a preferred embodiment of the present invention, the mass ratio of the coating material to the first halide solid electrolyte particles is (0.005-0.05):1.

[0043] According to the present invention, the D50 of the halide solid electrolyte composite material particles can be 10.1 to 22 μm. Suitable D50 of halide solid electrolyte composite material particles can have high ionic conductivity, which helps to achieve the battery rate performance; and can form a dense and good contact with the positive electrode material, which can effectively reduce the interface side reaction, improve the positive electrode capacity and battery cycle performance.

[0044] According to the present invention, the first halide solid electrolyte in the present invention is a crystalline halide electrolyte, and the particle size needs to be larger than the coating layer material, while taking into account the higher ionic conductivity. If the particle size of the first halide solid electrolyte particles is too small, the electrolyte ion conductivity will be low and it will be difficult to achieve uniform coating; if the particle size is too large, the contact between the electrolyte material and the positive electrode material will be affected, and the performance of the positive electrode will be affected. The D50 of the first halide solid electrolyte particles can be 10 to 20 μm. Exemplarily, the D50 of the first halide solid electrolyte particles can be any value of 10 μm, 12 μm, 14 μm, 16 μm, 18 μm and 20 μm, or any value within the range of any two of the above values. Preferably, the D50 of the first halide solid electrolyte particles is 10 to 12 μm.

[0045] According to the present invention, the second halide solid electrolyte particles are used as coating materials, and the particle size needs to be smaller than the core material. The second halide solid electrolyte particles form a relatively dense coating layer while taking into account a certain ionic conductivity. If the particle size of the second halide solid electrolyte particles is too small, the coating layer will be too dense, affecting the electrolyte ion conductivity and performance; if the particle size of the second halide solid electrolyte particles is too large, the coating layer will be uneven, and the coating effect will not be achieved, affecting the stability of the electrolyte and the positive electrode. The D50 of the second halide solid electrolyte particles can be 0.05 to 1 μm. Exemplarily, the D50 of the second halide solid electrolyte particles can be any value in 0.05 μm, 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm and 1 μm, or any value in the range of any two of the above values. Preferably, the D50 of the second halide solid electrolyte particles is 0.05 to 5 μm.

[0046] A second aspect of the present invention provides a method for preparing a halide solid electrolyte composite material, the method comprising the following steps:

[0047] S1, mixing a crystalline halide electrolyte suspension and an amorphous halide electrolyte suspension and performing a dispersion treatment to obtain a first material; stirring the first material to obtain a second material;

[0048] S2, drying the second material to obtain a precursor;

[0049] S3, subjecting the precursor to heat treatment and grinding treatment.

[0050] According to the present invention, the crystalline halide electrolyte suspension may include a crystalline halide electrolyte and a first organic solvent. The solid content of the crystalline halide electrolyte suspension in the present invention may be 20-50%; optionally, the first solvent is selected from at least one of an alkane solvent, a benzene solvent, an ether solvent and a ketone solvent; preferably, the first solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone.

[0051] According to the present invention, the amorphous halide electrolyte suspension may include an amorphous halide electrolyte and a second organic solvent. The solid content of the amorphous halide electrolyte suspension in the present invention may be 0.5-20%; optionally, the second solvent is selected from at least one of an alkane solvent, a benzene solvent, an ether solvent and a ketone solvent; preferably, the second solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone.

[0052] The preparation method of the crystalline halide electrolyte suspension and the amorphous halide electrolyte suspension in the present invention preferably adopts liquid phase coating, and the liquid phase coating method is conducive to uniform mixing, forming a uniform suspension, and achieving uniform coating; it is more efficient, and there is no need to pause for several manual scraping processes; it is more conducive to the use of existing equipment or easier to develop special equipment, and more conducive to achieving large-scale production. Exemplarily, the preparation of the crystalline halide electrolyte suspension in the present invention may include: mixing and stirring a crystalline halide electrolyte with a first organic solvent. Wherein, the stirring rate may be 50 to 300 r / min, and the time may be 2 to 6h. The preparation of the amorphous halide electrolyte suspension in the present invention may include: mixing and stirring an amorphous halide electrolyte with a second organic solvent. Wherein, the stirring rate may be 50 to 300 r / min, and the time may be 2 to 6h.

[0053] According to the present invention, in step S1, the mixing and the dispersing treatment are performed in a first inert atmosphere.

[0054] In the present invention, in order to ensure the uniformity of mixing, the step of mixing the crystalline halide electrolyte suspension with the amorphous halide electrolyte suspension may include: while keeping the crystalline halide electrolyte suspension in a stirring state, adding the amorphous halide electrolyte suspension into the crystalline halide electrolyte suspension in small amounts.

[0055] In the present invention, suitable dispersion treatment conditions are conducive to uniform coating and improved coating efficiency. If the temperature is too low, the reaction time needs to be extended, affecting the coating efficiency; if the temperature is too high, the solvent will evaporate and lose during the reaction, affecting the coating effect. Exemplarily, the dispersion treatment conditions may include: a dispersion temperature of 50 to 80°C and a dispersion time of 2 to 6 hours.

[0056] In the present invention, the stirring treatment is carried out in a second inert atmosphere. The purpose of the stirring treatment is to volatilize the solvent to obtain a viscous slurry for subsequent steps. If the temperature of the stirring treatment is too low, the solvent evaporates slowly, increasing the reaction time; if the temperature is too high, the solvent evaporates quickly and affects the performance of the electrolyte. Exemplarily, the conditions for the stirring treatment may include: a stirring temperature of 50 to 80°C and a stirring time of 2 to 6 hours.

[0057] According to the present invention, in step S2, the drying process is carried out in a third inert atmosphere; in order to improve efficiency and reduce solvent residue, the drying process is preferably a freeze drying process. Exemplarily, the freeze drying process conditions may include: a freezing temperature of -100 to -20°C, a drying time of 6 to 12 hours, and a pressure of -95 to -50Pa.

[0058] According to the present invention, in step S3, the heat treatment is performed in a fourth inert atmosphere; the conditions of the heat treatment may include: a temperature of 100 to 250° C., a heating rate of 1 to 2° C. / min, and a time of 2 to 4 hours.

[0059] The first inert atmosphere, the second inert atmosphere, the third inert atmosphere and the fourth inert atmosphere involved in the present invention are inert atmospheres well known in the art. For example, the first inert atmosphere, the second inert atmosphere, the third inert atmosphere and the fourth inert atmosphere can be independently selected from at least one of nitrogen, argon and helium.

[0060] In one embodiment of the present invention, the preparation method of the halide solid electrolyte composite material may include the following steps: weigh a certain amount of crystalline halide electrolyte and amorphous halide electrolyte according to the ratio and put them into a stirring tank respectively, and then add a certain amount of solvent respectively, the process control of the two is the same, and stir at a speed of 50 to 300 r / min for 2 to 6 hours, and after the end, a uniform crystalline halide electrolyte suspension and an amorphous halide electrolyte suspension are obtained respectively. The stirring tank containing the crystalline halide electrolyte suspension is transferred to an oil bath device, the temperature is controlled at 50 to 80°C, and the stirring speed remains unchanged; then the amorphous halide electrolyte suspension is added gradually with a straw, and after the addition is completed, the stirring speed is kept unchanged and the stirring is continued for 2 to 6 hours to obtain the first material, and then the oil bath temperature is increased to 100 to 200°C, and the stirring is continued until the slurry becomes viscous to obtain the second material. The second material is transferred to a freeze dryer, the temperature is controlled at -100 to -20°C, the vacuum is controlled at ~95 to -50Pa, the drying time is 6 to 12 hours, and the precursor is obtained after completion. The precursor is transferred to a tubular furnace for heat treatment, the heat treatment temperature is 100 to 250°C, the heating rate is 1 to 2°C / min, the insulation time is 2 to 4 hours, and the electrolyte rough product is obtained after natural cooling. The rough product is ground and sieved to obtain the electrolyte product.

[0061] A third aspect of the present invention provides a battery, wherein the battery contains a solid electrolyte, wherein the solid electrolyte includes the above-mentioned halide solid electrolyte composite material and / or the halide solid electrolyte composite material prepared according to the above-mentioned method.

[0062] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.

[0063] Example 1

[0064] 1) Under the protection of argon atmosphere, weigh 10 g of LiNbOCl4 and put it into a stirring tank 1, add 40 g of trimethylbenzene solvent and stir at a stirring speed of 200 rpm for 2 h to obtain a crystalline halide electrolyte suspension with a solid content of 20%; simultaneously weigh 0.05 g of LiTaCl5O 0.5 The halide electrolyte was placed in a stirring tank 2, and 5 g of trimethylbenzene solvent was added and stirred at a stirring speed of 200 rpm for 2 h to obtain an amorphous halide electrolyte suspension having a solid content of 0.99%.

[0065] 2) Transfer the stirring tank containing the crystalline halide electrolyte suspension to an oil bath device, control the temperature at 60°C, and keep the stirring speed constant; then add the halide electrolyte suspension gradually with a pipette, keep the stirring speed constant and continue stirring for 4 hours to obtain the first material; then increase the oil bath temperature to 120°C, continue stirring until the slurry becomes viscous, and obtain the second material.

[0066] 3) Under an argon atmosphere, the second material was transferred to a freeze dryer, the temperature was controlled at -75°C, the vacuum was controlled at -85Pa, the drying time was 8 hours, and a precursor was obtained after the drying;

[0067] 4) Under an argon atmosphere, the precursor was transferred to a tube furnace for heat treatment at a temperature of 150° C., a temperature rise rate of 1° C. / min, and a holding time of 4 h. After natural cooling, a crude electrolyte product was obtained.

[0068] 5) Grinding the coarse finished product and passing it through a 500-mesh sieve to obtain a halide electrolyte material with an overall particle size of ≤25 μm.

[0069] Example 2

[0070] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.1 g.

[0071] Example 3

[0072] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.15 g.

[0073] Example 4

[0074] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.2 g.

[0075] Example 5

[0076] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.25 g.

[0077] Example 6

[0078] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5The amount of halide electrolyte used was 0.3 g.

[0079] Example 7

[0080] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.35 g.

[0081] Example 8

[0082] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.4 g.

[0083] Example 9

[0084] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.45 g.

[0085] Example 10

[0086] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.5 g.

[0087] Embodiment 11

[0088] The preparation method of the halide electrolyte material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiTaCl5O 0.5 The amount of halide electrolyte used was 0.8 g.

[0089] Comparative Example 1

[0090] LiNbOCl4 was used as the halide electrolyte in this comparative example.

[0091] Comparative Example 2

[0092] Using LiTaCl5O 0.5 As the halide electrolyte of this comparative example.

[0093] The composition information of the halide electrolytes in Examples 1 to 11 and Comparative Examples 1 to 2 is shown in Table 1. The D50 of the crystalline halide electrolyte particles and the D50 of the amorphous halide electrolyte particles can be measured by SEM electron microscopy.

[0094] Table 1

[0095]

[0096] Test Example 1

[0097] The halide electrolyte materials prepared in Examples 1 to 11 and Comparative Examples 1 to 2 were subjected to performance tests. The test results are shown in Tables 2 and Figure 1 .

[0098] Ionic conductivity test: Weigh 100 mg of electrolyte powder, put it in an insulating sleeve with an inner diameter of 10 mm, press it at a pressure of 300 MPa, and perform an AC impedance spectrum test to measure the impedance value of the electrolyte material. Then perform a thickness test on the pressurized sheet electrolyte, and calculate the ionic conductivity of the electrolyte material based on the impedance value, thickness value and area of ​​the sheet using the formula σ=d / (R*S), where σ is the ionic conductivity, in units of s / cm; d is the thickness of the sheet, in units of cm; R is the impedance value, in units of Ω; S is the area of ​​the sheet, in units of cm 2 The test results are shown in Table 2.

[0099] Air stability test: After the same batch of electrolytes is tested for ion conductivity as above, 100 mg of electrolyte powder is sampled and placed in an environment with a temperature of 25±3°C and a dew point of ≤-55°C for 6 hours. After the standing period, the electrolyte ion conductivity is retested and the ion conductivity retention ratio is calculated; if the ion conductivity retention ratio is ≥95%, it means that the electrolyte has high air stability. The test results are shown in Table 2.

[0100] Target electrolyte voltage window test: The target electrolyte and conductive carbon powder were weighed at a weight ratio of 70:30 and ground evenly using an agate mortar. 20 mg of the target electrolyte-conductive carbon powder mixture and 20 mg Li 5.4 PS 4.4 Cl 1.6 The electrolyte is stacked. It is pressed at a pressure of 360MPa, and then 5.4 PS 4.4 Cl 1.6 A lithium foil is stacked on the side and pressed at a pressure of 100 MPa. Then, stainless steel collectors are placed on the upper and lower sides of the stack, and collector leads are attached to the collectors. Linear sweep voltammetry test is performed with a scan range of 2 to 5 V and a scan rate of 0.1 mV / S. A tangent is drawn to the oxidation peak of the test curve, and the intersection with the horizontal axis is the oxidation potential of the material. The test results are shown in Table 2.

[0101] Battery test: In an argon glove box, the target electrolyte, positive electrode active material Li (Ni 0.8 Co 0.1 Mn 0.1)O2(NCM811) were weighed at a weight ratio of 20:80. They were ground evenly using an agate mortar to produce a composite positive electrode material. 14 mg of the composite positive electrode material, 70 mg of Li 5.4 PS 4.4 Cl 1.6 The electrolyte is stacked. It is press-formed at a pressure of 360MPa to obtain a positive electrode and a solid electrolyte layer. Next, a piece of aluminum foil is stacked on the positive electrode side, thereby forming a collector on the positive electrode side. Then, on the opposite side of the solid electrolyte layer in contact with the positive electrode, an indium sheet with a thickness and diameter of 200μm and 10mm is placed as a negative electrode material. It is press-formed at a pressure of 80MPa to produce a stack consisting of a positive electrode, a solid electrolyte layer and a negative electrode. Then, stainless steel collectors are arranged on the upper and lower parts of the stack, and collector leads are attached to the collectors. The assembled solid-state battery was subjected to a cycle performance test, and the test conditions were: current density of 1C, voltage range of 2.7~4.3V (Li+ / Li). The test is shown in Table 2.

[0102] XRD was performed on Examples 6 to 11 and Comparative Example 1. The XRD patterns are shown in Figure 1 .

[0103] Table 2

[0104]

[0105]

[0106] Combining the data in Table 1 and Table 2, it can be seen from Examples 1 to 11 and Comparative Examples 1 to 2 that: as the coating amount increases, the ionic conductivity of the target electrolyte decreases first and then tends to stabilize. When the coating amount is ≥4.5%, the ionic conductivity of the target electrolyte is basically consistent with the amorphous halide electrolyte of the coating layer, indicating that the coating layer is completely dense at this time; the oxidation potential shows a trend of gradually increasing first and then tending to stabilize. When the coating amount is ≥3.5%, the oxidation potential of the target electrolyte is basically consistent with the amorphous halide electrolyte of the coating layer, indicating that the coating effect is good at this time; the battery performance shows a trend of first increasing and then decreasing. When the coating amount reaches 3.5 % (Example 7), the target electrolyte oxidation potential reaches a maximum value of 4.39V, the ionic conductivity is still at a relatively high level of 6.6mS / cm, and the battery performance is optimal (first efficiency 95.2%, first week discharge capacity 210.8mAh / g, 200-week cycle capacity retention rate 98.5%); the air stability shows a trend of first increasing and then slightly decreasing, and is highest when the coating amount is 3.5%, that is, the ionic conductivity retention rate after exposure can reach 98.5%; when the coating amount is greater than 3.5%, the ionic conductivity retention rate after exposure is based on stabilization and a slight downward trend, which once again shows that the coating is complete and dense under the condition of a coating amount of 3.5%.

[0107] At the same time, combined with XRD test results (such as Figure 1 As shown, with the increase of the coating amount, the characteristic peaks of the crystalline halide electrolyte phase gradually decrease or the peak intensity decreases. When the coating amount is ≥3.5%, the target electrolyte XRD test shows an amorphous phase, which is consistent with the amorphous halide electrolyte phase of the coating layer, indicating that the coating is complete and dense under the condition of a coating amount of 3.5%, and the coating process is a physical process without chemical reaction. In addition, by comparing Examples 1 to 11 with Comparative Examples 1 to 2, it can be seen that whether the crystalline or amorphous halide electrolyte is used alone as the positive electrode side electrolyte material, the battery performance is poor.

[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A halide solid electrolyte composite material, characterized in that: The halide solid electrolyte composite material comprises a first halide solid electrolyte particle and a coating layer coated on the surface of the first halide solid electrolyte particle; Wherein, the first halide solid electrolyte particles are crystalline halide electrolyte particles; The coating layer includes second halide solid electrolyte particles, and the second halide solid electrolyte particles are amorphous halide electrolyte particles.

2. The halide solid electrolyte composite material according to claim 1, characterized in that: The first halide solid electrolyte particles include LiMOCl4, wherein M is selected from Ta and / or Nb; And / or, the second halide solid electrolyte particles include LiTaCl5N 1 / n , wherein N is selected from at least one of Cl, Br, F and O, and n=1 or 2.

3. The halide solid electrolyte composite material according to claim 1, characterized in that: The mass ratio of the coating layer material to the first halide solid electrolyte particles is (0.001-0.1):

1.

4. The halide solid electrolyte composite material according to claim 1, characterized in that: The D50 of the halide solid electrolyte composite material particles is 10.1 to 22 μm; Optionally, the D50 of the first halide solid electrolyte particles is 10-20 μm; the D50 of the second halide solid electrolyte particles is 0.05-1 μm.

5. A method for preparing the halide solid electrolyte composite material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, mixing a crystalline halide electrolyte suspension and an amorphous halide electrolyte suspension and performing a dispersion treatment to obtain a first material; stirring the first material to obtain a second material; S2, drying the second material to obtain a precursor; S3, subjecting the precursor to heat treatment and grinding treatment.

6. The preparation method according to claim 5, characterized in that: The crystalline halide electrolyte suspension comprises a crystalline halide electrolyte and a first organic solvent; the solid content of the crystalline halide electrolyte suspension is 20 to 50%; Optionally, the first solvent is selected from at least one of an alkane solvent, a benzene solvent, an ether solvent and a ketone solvent; preferably, the first solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone; and / or, The amorphous halide electrolyte suspension comprises an amorphous halide electrolyte and a second organic solvent; the solid content of the amorphous halide electrolyte suspension is 0.5 to 20%; Optionally, the second solvent is selected from at least one of alkane solvents, benzene solvents, ether solvents and ketone solvents; preferably, the second solvent is selected from at least one of dichloromethane, n-heptane, p-xylene, trimethylbenzene, anisole, monochlorobenzene and cyclohexanone.

7. The preparation method according to claim 5, characterized in that: In step S1, the mixing and the dispersing treatment are performed in a first inert atmosphere; the conditions of the dispersing treatment include: a dispersing temperature of 50 to 80° C. and a dispersing time of 2 to 6 hours; The stirring treatment is carried out in a second inert atmosphere; the conditions of the stirring treatment include: a stirring temperature of 50 to 80° C. and a stirring time of 2 to 6 hours.

8. The preparation method according to claim 5, characterized in that: In step S2, the drying process is carried out in a third inert atmosphere; the drying process is a freeze-drying process, and the conditions of the freeze-drying process include: a freezing temperature of -100 to -20°C, a drying time of 6 to 12 hours, and a pressure of -95 to -50Pa.

9. The preparation method according to claim 5, characterized in that: In step S3, the heat treatment is performed in a fourth inert atmosphere; the conditions of the heat treatment include: a temperature of 100 to 250° C., a heating rate of 1 to 2° C. / min, and a time of 2 to 4 hours.

10. A battery, characterized in that: The battery contains a solid electrolyte, and the solid electrolyte includes the halide solid electrolyte composite material according to any one of claims 1 to 4 and / or the halide solid electrolyte composite material prepared by the method according to any one of claims 5 to 9.

Citation Information

Cited By

  • Positive electrode material and preparation method thereof, positive plate and battery

    CN119569137A